A Needs Analysis for Developing an Academic Supervision Model for School Principals Grounded in Local Wisdom - Hasmiati, Hasmiati; Tolla, Ismail; Wahira, Wahira (International Journal of Technology and Education Research, 2025)
This study aims to analyze the need for the development of a school principal's academic supervision model as an effort to improve the quality of learning through teacher coaching. The background of this research is based on the phenomenon that the implementation of academic supervision in schools still faces various obstacles, such as limited suitability with teachers' needs, lack of openness, lack of feedback, and approaches that are not fully relevant to teacher characteristics. This study uses a descriptive approach by combining quantitative and qualitative analysis. The subjects of the study were teachers and principals who were selected using the purposive sampling technique. Data were collected through observation, questionnaires, interviews, and documentation studies, then analyzed using descriptive statistics for quantitative data and thematic analysis for qualitative data. The results of the study show that most teachers consider that the academic supervision carried out by school principals is still not in accordance with the real needs in the field. In terms of openness and transparency, more than half of the respondents assessed that supervision had not been fully implemented openly. In terms of feedback, even though some teachers have received constructive input, there are still teachers who feel that they are lacking or do not get feedback after supervision. Other findings show that the supervision approach that teachers are most interested in is based on local wisdom, followed by peer approaches and the use of technology. The conclusion of this study emphasizes the need to develop a more adaptive, participatory, and needs-based academic supervision model.